2019
DOI: 10.1016/j.bbmt.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Transplant-Associated Thrombotic Microangiopathy Is a Multifactorial Disease Unresponsive to Immunosuppressant Withdrawal

Abstract: Transplant-associated thrombotic microangiopathy (TA-TMA) after allogeneic hematopoietic cell transplantation (HCT) has not been well characterized in large population studies with clinically adjudicated cases. We performed a retrospective cohort study of adults who underwent allogeneic HCT between 2006 and 2015 to determine the incidence of and risk factors for TA-TMA and to describe its natural history and response to immunosuppressant withdrawal management. Among 2145 patients in this study, 192 developed T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 27 publications
4
77
0
Order By: Relevance
“…Given this discrepancy between laboratory‐based and provider‐reported TMA diagnosis, we examined other single‐centre studies published during the same period as our study (2008–2016). Whereas one prospective study of predominantly paediatric patients reported a 1‐year cumulative incidence of 39% (Jodele et al , ), the remaining studies of adult patients reported a 6‐month to 1‐year cumulative incidence, ranging from 4 to 16% (Labrador et al , ; Sakellari et al , ; Ye et al , ; Postalcioglu et al , ; Li et al , ; Kraft et al , ). These incidences are higher than what was reported to the CIBMTR, which are likely a subset of mostly more severe cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Given this discrepancy between laboratory‐based and provider‐reported TMA diagnosis, we examined other single‐centre studies published during the same period as our study (2008–2016). Whereas one prospective study of predominantly paediatric patients reported a 1‐year cumulative incidence of 39% (Jodele et al , ), the remaining studies of adult patients reported a 6‐month to 1‐year cumulative incidence, ranging from 4 to 16% (Labrador et al , ; Sakellari et al , ; Ye et al , ; Postalcioglu et al , ; Li et al , ; Kraft et al , ). These incidences are higher than what was reported to the CIBMTR, which are likely a subset of mostly more severe cases.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, significant risk factors for TA‐TMA included ALL and aplastic anaemia (compared to AML), mismatched donor source (URD or CB), prior autologous transplant, CNI plus sirolimus as GVHD prophylaxis and grade II‐IV GVHD. The risk factors associated with TA‐TMA in our study are consistent with the previously published studies (Shimoni et al , ; Cutler et al , ; Martinez et al , ; Uderzo et al , ; Nakamae et al , ; Oran et al , ; Cho et al , ; Willems et al , ; Shayani et al , ; Labrador et al , ; Sakellari et al , ; Ye et al , ; Postalcioglu et al , ; Li et al , ; Kraft et al , ). Several other risk factors were also identified in this study, including African‐American race, aplastic anaemia, decreased baseline GFR and non‐ATG containing conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…TA-TMA can be caused by or amplified by graft-versus-host disease (GVHD), infections, or calcineurin inhibitors after allogeneic HSCT, all of which may complicate biological findings. [30][31][32][33] We opted to study a more homogeneous group of patients developing TA-TMA after autologous HSCT for neuroblastoma, in whom TA-TMA is uncomplicated by GVHD and calcineurin inhibitors and viral infections are markedly less frequent. The cause of endothelial injury in patients with neuroblastoma and TA-TMA is likely related to high-dose chemotherapy, and we were able to study children receiving exactly the same chemotherapy regimen to eliminate another potential source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The deviation of nonrenal and nonintestinal TA-TMA is also assumed to be due to the small sample size because a previous study found that a few of the autopsied patients who had renal TA-TMA were also reported to be having nonrenal and nonintestinal TA-TMA [22]. Several risk factors have been considered regarding TA-TMA, including conditioning agents, radiation, calcineurin inhibitors, infection, and GVHD [23,[34][35][36][37][38][39][40][41][42]. However, the results were conflicting, and the degree to which any of these factors affects the occurrence or the progression of TA-TMA in individuals is still remarkably unclear.…”
Section: Discussionmentioning
confidence: 99%